Patterning the vertebrate heart - Harvey, Richard P. (Nature reviews. Genetics, 2002)
The mammalian heart is crafted from a few progenitor cells that are subject to rapidly changing sets of instructions from their environment and from within. These instructions cause them to migrate, expand and diversify in lineage, and acquire form and function. Molecular information from various model systems, combined with increasingly detailed morphogenetic data, has provided insights into some of these key events. Many congenital heart abnormalities might arise from defects in the early stages of heart development, therefore it is important to understand the molecular pathways that underlie the lineage specification and patterning processes that shape this organ.